2017
DOI: 10.3923/pjn.2017.273.278
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Mixing Wheat Flour with Pumpkin and Dates on the Nutritional and Sensory Characteristics of Cake

Abstract: Background: The development of food products is a major goal of the food industry. Pumpkin is a rich source of nutrients that may help improve products. Objective: The aim of this study was to evaluate the effect of replacing wheat flour with pumpkin or both pumpkin and dates on the chemical and sensory characteristics of cake. Methodology: Three different cakes were prepared: (1) Control, (2) 50% of the wheat flour replaced with pumpkin mash and (3) 50% of the wheat flour replaced with 30% pumpkin and 20% dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 15 publications
1
3
0
Order By: Relevance
“…General acceptability result ranging from 2.74 -7.83 shows that cake produced from wheat/pumpkin composite flour had a good acceptability up to 70% substitution level as there was no significant difference between the control (100% wheat flour based cake) and up to 70% substitution level. Similar results were reported by Aljahani and Al-khurarieef [51] and Hosseini et al [52] for various sensory attributes evaluated in similar studies.The results of the sensory attributes of this present study showed that cakes can be substituted with up to 70% pumpkin flour based on general acceptability.…”
Section: Sensory Scoressupporting
confidence: 91%
“…General acceptability result ranging from 2.74 -7.83 shows that cake produced from wheat/pumpkin composite flour had a good acceptability up to 70% substitution level as there was no significant difference between the control (100% wheat flour based cake) and up to 70% substitution level. Similar results were reported by Aljahani and Al-khurarieef [51] and Hosseini et al [52] for various sensory attributes evaluated in similar studies.The results of the sensory attributes of this present study showed that cakes can be substituted with up to 70% pumpkin flour based on general acceptability.…”
Section: Sensory Scoressupporting
confidence: 91%
“…In study [29], pumpkin paste was used. Adding it to a cupcake in the volume of 27 % by weight of dough changed the properties of the product.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…The use of pumpkin as a natural coloring agent in pasta and flour mixes has also been found [5,6]. Due to the lack of dominant sensory characteristics, pumpkin flesh is an excellent addition to many other products [7,8]. The industrial food applications of pumpkins also include meat products (beef meatballs, chicken burgers, and low-fat meatballs), grain products (bread, cake, biscuits, cookies, muffins, and pasta), beverages (juice, pineapple juice, and smoothies), and dairy (yoghurt and ice cream) [1,[8][9][10].…”
Section: Introductionmentioning
confidence: 99%